Polymer solid electrolyte and its manufacturing method
Patent Information
- Application Number
- JP2024547114
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-05-31
- Filing Date
- 2023-05-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-05-31
AI Technical Summary
【0017】 本発明による高分子固体電解質は、高分子に含まれる架橋結合性官能基により形成された架橋結合構造及び無定形高分子鎖を含む構造により、高分子の結晶性が減少し、これによりイオン伝導度を向上させることができる。
Smart Images

Figure 2025505680000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0067041 filed on May 31, 2022 and Korean Patent Application No. 10-2023-0070049 filed on May 31, 2023, and incorporates all contents disclosed in the documents of said Korean patent applications as part of this specification.
[0002] The present invention relates to a polymer solid electrolyte and a method for producing the same. [Background technology]
[0003] Lithium secondary batteries that use liquid electrolytes have a structure in which the negative and positive electrodes are separated by a separator, and if the separator is damaged by deformation or external impact, a short circuit can occur, which can lead to risks such as overheating and explosion. Therefore, the development of a solid electrolyte that can ensure safety in the field of lithium secondary batteries is a very important issue.
[0004] Lithium secondary batteries using solid electrolytes have the advantages of improved battery safety and the prevention of electrolyte leakage, which improves battery reliability and makes it easier to manufacture thin batteries. In addition, because lithium metal can be used as the negative electrode, the energy density can be improved, and it is expected to be used in small secondary batteries as well as high-capacity secondary batteries for electric vehicles, and is attracting attention as a next-generation battery.
[0005] Among solid electrolytes, polymeric solid electrolytes may be made from ion-conductive polymer materials, and hybrid materials in which polymeric and inorganic materials are mixed have also been proposed. The inorganic material may be an inorganic material such as an oxide or sulfide.
[0006] Such conventional polymer solid electrolytes are manufactured through a process of forming a coating film and then drying it at a high temperature. However, the conventional manufacturing technology for polymer solid electrolytes has a limitation in that it is difficult to manufacture a polymer solid electrolyte with improved ion conductivity due to the high crystallinity of crystalline polymers or semi-crystalline polymers. In other words, the higher the crystallinity of the polymer, the lower the chain mobility of the polymer. As a result, the movement of lithium ions inside the polymer solid electrolyte is restricted, making it difficult to improve the ion conductivity of the polymer solid electrolyte.
[0007] For example, a conventional polymer solid electrolyte can be manufactured by forming a coating film using polyvinyl alcohol (PVA) containing a hydroxyl group, which is a cross-linking functional group, as a polymer, and then performing a high-temperature drying process. Specifically, the PVA is dissolved in water to prepare a PVA aqueous solution, and the PVA aqueous solution is applied to a substrate by solution casting to form a coating film, and the coating film is dried at room temperature or at a high temperature to manufacture a PVA film-shaped polymer solid electrolyte. In this case, the high temperature may mean 80°C or higher, which is the glass transition temperature (Tg) of PVA. In the drying process, after the water evaporates, hydrogen bonds are formed between the cross-linking functional groups contained in the PVA, and the hydrogen bonds cause chain folding of the polymer chain, resulting in a phenomenon in which the crystallinity of the polymer film is increased. The higher the crystallinity, the more brittle the polymer film is formed. In a polymer film with high crystallinity and brittleness, the chain mobility of the polymer chain is reduced, and when dissociated ions exist inside the polymer film, the mobility of the ions is also significantly reduced. For this reason, a typical PVA film produced by forming a coating film and then drying it at a high temperature as described above exhibits physical properties that are not suitable for use as a polymer solid electrolyte for lithium secondary batteries.
[0008] To overcome these limitations of conventional polymer solid electrolytes, a technology has been developed to improve the mobility of polymer chains by adding a plasticizer to a crystalline or semi-crystalline polymer, thereby improving the ionic conductivity of the polymer solid electrolyte. However, when using a plasticizer, it is necessary to ensure appropriate dispersion and solubility between the polymer and the plasticizer, which can make it difficult to set process conditions. In addition, when a liquid plasticizer is used, the compatibility with the polymer decreases, making it difficult to carry out the manufacturing process of the polymer solid electrolyte.
[0009] For this reason, there is a need to develop technology that can improve the ionic conductivity of polymer solid electrolytes without the use of separate additives such as plasticizers. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] China Patent Publication No. 112259788 Summary of the Invention [Problem to be solved by the invention]
[0011] An object of the present invention is to provide a polymer solid electrolyte having improved ionic conductivity.
[0012] Another object of the present invention is to provide a method for producing a polymer solid electrolyte having improved ionic conductivity.
[0013] Another object of the present invention is to provide an all-solid-state battery including a solid polymer electrolyte with improved ionic conductivity. [Means for solving the problem]
[0014] In order to achieve the above object, the present invention provides a polymer solid electrolyte comprising a polymer having a cross-linkable functional group, a lithium salt, and a solvent, the polymer solid electrolyte comprising a cross-linked structure; and an amorphous polymer chain having the cross-linkable functional group, the cross-linked structure comprising (a) a cross-link between the cross-linkable functional groups, (b) a cross-link between the cross-linkable functional group and the solvent, and (c) a bond between the cross-linkable functional group and the lithium salt.
[0015] The present invention also provides a method for producing the polymer solid electrolyte, the method comprising: (S1) adding a lithium salt to a polymer solution containing a cross-linkable functional group to form a polymer solid electrolyte-forming solution; (S2) coating the polymer solid electrolyte-forming solution on a substrate to form a coating film; and (S3) freezing and thawing the coating film.
[0016] The present invention also provides an all-solid-state battery comprising the polymer solid electrolyte. Effect of the Invention
[0017] The polymer solid electrolyte according to the present invention has a cross-linked structure formed by cross-linking functional groups contained in the polymer and a structure including an amorphous polymer chain, thereby reducing the crystallinity of the polymer and improving the ionic conductivity.
[0018] In addition, the polymer solid electrolyte exhibits physical properties such as reduced brittleness and increased ductility and viscosity due to the structural characteristics. [Brief description of the drawings]
[0019] [Figure 1] 1 is a graph showing the tendency of the ionic conductivity of the electrolyte depending on the molar ratio ([Li] / [OH]) of the cross-linkable functional group and the lithium salt. [Diagram 2] 1 is a photograph showing the electrolyte morphology depending on the molar ratio of cross-linking functional groups to lithium ([Li] / [OH]). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will now be described in further detail to aid in understanding the invention.
[0021] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.
[0022] The term "crosslinked structure" as used herein refers to a structure including a three-dimensional frame formed by polymer chains and an internal space of the frame. The polymer chains may be formed by crosslinking involving crosslinking functional groups contained in the polymer. The crosslinked structure has a three-dimensional shape and is in a form in which the polymer chains are intertwined with each other, so it can also be called a three-dimensional network structure.
[0023] Polymer solid electrolyte The present invention relates to a polymer solid electrolyte. The polymer solid electrolyte of the present invention is a polymer solid electrolyte comprising a polymer having a cross-linkable functional group, a lithium salt, and a solvent, the polymer solid electrolyte comprising a cross-linked structure and an amorphous polymer chain having the cross-linkable functional group, the cross-linked structure comprising (a) a cross-link between the cross-linkable functional groups, (b) a cross-link between the cross-linkable functional group and the solvent, and (c) a bond between the cross-linkable functional group and the lithium salt. Specifically, the amorphous polymer chain and the lithium salt are contained in an internal space formed in the cross-linked structure, and the lithium salt is contained in a dissociated state.
[0024] The cross-linked structure may be formed by a freezing process as described below. In the freezing process, a part of the cross-linking functional groups contained in the polymer may form localized crystallites, and the localized crystallites may act as cross-linkable junction points to cross-link, thereby forming the cross-linked structure. In this case, the microcrystals refer to a shape resembling a knot formed by entangling threads, unlike a crystal structure formed by folding of polymer chains.
[0025] In the present invention, the (a) cross-linking bond between the cross-linking functional groups may include a hydrogen bond between the cross-linking functional groups, and for example, the hydrogen bond may be a hydrogen bond between OH-.
[0026] If the cross-linked structure is composed only of cross-links between the (a) cross-linkable functional groups, crystallinity may occur in the polymer solid electrolyte, resulting in a decrease in ion conductivity.
[0027] However, since the cross-linked structure includes not only the (a) cross-linking between the cross-linking functional groups, but also the (b) cross-linking between the cross-linking functional group and the solvent, and the (c) bond between the cross-linking functional group and the lithium salt, the occurrence of crystallinity in the polymer solid electrolyte can be prevented.
[0028] In the present invention, the cross-linking between the (b) cross-linkable functional group and the solvent may include a hydrogen bond, for example, the hydrogen bond may be a hydrogen bond between OH- and H+, where H+ may be derived from the water solvent.
[0029] The (b) cross-linking between the cross-linkable functional group and the solvent may refer to hydrogen bonding between a portion of the solvent remaining after the freezing and thawing process and the cross-linkable functional group.
[0030] In addition, the crosslinking between the (b) crosslinkable functional group and the solvent prevents crosslinking between the (a) crosslinkable functional groups and prevents the crosslinked structure from being composed only of crosslinks between the (a) crosslinkable functional groups, thereby preventing an increase in crystallinity of the polymer solid electrolyte.
[0031] In the present invention, the bond between the (c) cross-linkable functional group and the lithium salt may include a bond due to Lewis acid-base interaction, and for example, the bond may be a bond between OH- and Li+.
[0032] The bond between the (c) cross-linkable functional group and the lithium salt prevents the cross-linking between the (a) cross-linkable functional groups and the (b) cross-linking between the cross-linkable functional group and the solvent, and prevents the cross-linked structure from being composed only of the cross-linking between the (a) cross-linkable functional groups, thereby preventing the occurrence of crystallinity in the polymer solid electrolyte and promoting the formation of amorphous polymer chains. As the amorphous polymer chains are formed, the mobility of the polymer chains is improved, and the hopping effect of the lithium ions is increased, thereby improving the ionic conductivity of the polymer solid electrolyte.
[0033] In the present invention, the amorphous polymer chain can also be formed by a freezing process as described below, and refers to a polymer chain that does not form crystals due to regular folding of the polymer chain and exists in a free state. That is, the amorphous polymer chain may include a polymer that includes a cross-linking functional group that does not form a bond such as (a), (b) and (c).
[0034] Due to the cross-linked structure, the polymer solid electrolyte is not easily broken or destroyed, and can therefore function as an electrolyte support that stably contains lithium ions.
[0035] In addition, the amorphous polymer chains allow the polymer solid electrolyte to exhibit elasticity and minimize brittleness, which is a property that the electrolyte is easily broken. In addition, the polymer chain mobility is excellent, and mobility of lithium ions within the electrolyte is improved, thereby providing a polymer solid electrolyte with improved ion conductivity.
[0036] In the present invention, the cross-linkable functional group contained in the polymer containing the cross-linkable functional group may have the property of forming a cross-linked structure by forming bonds such as (a), (b) and (c).
[0037] For example, the cross-linkable functional group may include one or more selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.
[0038] The weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group may be 80,000 g / mol to 130,000 g / mol, specifically, 80,000 g / mol or more, 83,000 g / mol or more, or 85,000 g / mol or more, and 90,000 g / mol or less, 110,000 g / mol or less, or 130,000 g / mol or less. If the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group is less than 80,000 g / mol, the bond due to the crosslinkable functional group may not be formed sufficiently to obtain a crosslinked structure. If the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group exceeds 130,000 g / mol, the entanglement of the polymer chain increases in the polymer solution used in the manufacturing process, and the solvent penetration rate into the inside of the polymer chain decreases. As a result, gelation of the polymer is accelerated, the solubility of the polymer is reduced, and the cross-linking functional groups are not smoothly bonded, so that it may be difficult to form a cross-linked structure.
[0039] In addition, the polymer containing the cross-linking functional group may have a feature that phase separation between the polymer and a solvent is smoothly performed in the polymer solution used in the manufacturing process, and the bonds (a), (b), and (c) are successfully formed by the cross-linking functional group contained in the phase-separated polymer upon freezing.
[0040] For example, the polymer containing a cross-linkable functional group may include at least one selected from the group consisting of polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(ethylene oxide), poly(acrylic amide), poly(acrylic acid) (PAA), starch-carboxymethyl cellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated PEG. Preferably, the polymer containing a cross-linkable functional group may be PVA, and the PVA may be advantageous in that phase separation between the PVA and a solvent is efficiently performed upon freezing during the process of producing a polymer solid electrolyte, and a cross-linked structure is formed by the bonds (a), (b), and (c) derived from the cross-linkable functional group of the PVA that has phase-separated from the solvent.
[0041] In the present invention, the lithium salt is contained in a dissociated state in the internal space of the cross-linked structure, and can improve the ionic conductivity of the polymer solid electrolyte.
[0042] In addition, the lithium salt forms a bond with the (c) cross-linking functional group and lithium salt, thereby preventing the occurrence of crystallinity in the polymer solid electrolyte and promoting the formation of amorphous polymer chains.
[0043] The lithium salts include (CF3SO2)2NLi (Lithium bis(trifluoromethanesulphonyl)imide, LiTFSI), (FSO2)2NLi (Lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, and LiC(CF3SO2)3.
[0044] In the present invention, the molar ratio ([Li] / [G]) of the crosslinkable functional group ([G]) of the polymer containing the crosslinkable functional group and the lithium ([Li]) of the lithium salt contained in the polymer solid electrolyte may be more than 0.1 and less than 0.5, specifically, more than 0.1, 0.2 or more, or 0.3 or more, and may be 0.4 or less, or less than 0.5. If the molar ratio ([Li] / [G]) is 0.1 or less, the content of the lithium salt may decrease, and the ionic conductivity of the polymer solid electrolyte may decrease, and if it is 0.5 or more, the content of the polymer containing the crosslinkable functional group may decrease, and the bonds of (a), (b), and (c) may not be sufficiently formed, which may increase the crystallinity and decrease the ionic conductivity. If the crosslinkable functional group is a hydroxyl group (OH-), the [G] may be expressed as [OH] or [O].
[0045] In the present invention, the polymer solid electrolyte may be in the form of a free-standing film or a coating layer. The free-standing film means a film that can maintain a film shape by itself without a separate support at room temperature and pressure. The coating layer means a layer obtained by coating on a substrate. When the polymer solid electrolyte is in the form of a coating layer, the coating layer may be in the form of a layer coated on an electrode.
[0046] The free-standing film or coating layer exhibits elasticity and minimizes brittleness, and has properties as a support that stably contains lithium ions, making it a suitable form for a polymer solid electrolyte.
[0047] In the present invention, the ionic conductivity of the polymer solid electrolyte is 10 -4 It may be S / cm or more.
[0048] The polymer solid electrolyte has low crystallinity and high ionic conductivity due to its structural characteristics including the cross-linked structure as described above, and as a result, despite being a solid electrolyte, it exhibits ionic conductivity at a level equal to or higher than that of conventional liquid electrolytes, thereby improving the performance of all-solid-state batteries.
[0049] In the present invention, the polymer solid electrolyte may further include a liquid electrolyte, which can further improve the ionic conductivity of the polymer solid electrolyte. The liquid electrolyte may also be contained in the inner space of the cross-linked structure.
[0050] The liquid electrolyte may be a liquid electrolyte commonly used in the art, and the composition of the liquid electrolyte is not particularly limited as long as it can be used in a lithium secondary battery. For example, the liquid electrolyte may include a lithium salt and a non-aqueous solvent. The lithium salt may be any one of the lithium salts described above. The non-aqueous solvent may include one or more selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), vinylene carbonate (VC), diethyl carbonate (DEC), dimethyl carbonate (DMC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTHF), dioxolane (DOX), dimethoxyethane (DME), diethoxyethane (DEE), γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane.
[0051] The liquid electrolyte may be contained in an amount of 1 to 5 wt % based on the total weight of the polymer solid electrolyte. If the content of the liquid electrolyte is 1 wt % or less, the effect of improving ion conductivity may be insignificant, and if it exceeds 5 wt %, the stability may decrease.
[0052] The above-mentioned polymer solid electrolyte may be prepared in a form including an amorphous polymer chain including a polymer having a cross-linked structure due to bonds such as (a), (b) and (c) formed by the cross-linking functional group contained in the polymer and a cross-linking functional group that does not form a cross-link. Due to such morphological characteristics, the polymer solid electrolyte can act as a support that stably contains lithium ions, exhibit elasticity and minimize brittleness, and can improve ion conductivity by preventing the occurrence of crystallinity.
[0053] Method for producing polymer solid electrolyte The present invention also relates to a method for producing a polymer solid electrolyte, comprising: (S1) adding a lithium salt to a polymer solution containing a cross-linking functional group to form a polymer solid electrolyte-forming solution; (S2) applying the polymer solid electrolyte-forming solution onto a substrate to form a coating film; and (S3) freezing and thawing the coating film.
[0054] In the method for producing the polymer solid electrolyte laminate, a cross-linking functional group contained in the polymer induces (a) cross-linking between cross-linking functional groups, (b) cross-linking between the cross-linking functional group and a solvent, and (c) bonding between the cross-linking functional group and a lithium salt through a freezing process without adding a plasticizer that is used to reduce the crystallinity of the polymer, thereby preventing crystallization of the polymer. As a result, a polymer solid electrolyte with improved ion conductivity can be produced.
[0055] Hereinafter, each step of the method for preparing a polymer solid electrolyte according to the present invention will be described in detail.
[0056] In the present invention, in the step (S1), a solution for forming a polymer solid electrolyte may be formed by adding a lithium salt to a polymer solution having a cross-linkable functional group. The types and properties of the polymer having a cross-linkable functional group and the lithium salt are as described above.
[0057] The solvent used in preparing the polymer solution may be a polar solvent, for example, water, that is, the polymer solution may be an aqueous polymer solution.
[0058] The concentration of the polymer solution containing a crosslinkable functional group can be appropriately adjusted in consideration of the degree to which the coating process can proceed smoothly when the polymer solid electrolyte forming solution is applied to a substrate. For example, the concentration of the polymer solution containing a crosslinkable functional group may be 5% to 20%, specifically, 5% or more, 7% or more, or 9% or more, and 13% or less, 17% or less, or 20% or less. If the concentration of the polymer solution containing a crosslinkable functional group is less than 5%, the concentration is too low and may flow down when applied to a substrate, and if it exceeds 20%, it is difficult to dissolve a lithium salt at a desired concentration in the polymer solution, and the viscosity is high, so it may be difficult to apply it in a uniform thin film.
[0059] In the present invention, in the step (S2), the polymer solid electrolyte forming solution can be applied onto a substrate to form a coating film.
[0060] The substrate is not particularly limited as long as it can serve as a support on which the polymer solid electrolyte forming solution is applied. For example, the substrate may be SS (stainless steel), a polyethylene terephthalate film, a polytetrafluoroethylene film, a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a vinyl chloride copolymer film, a polyurethane film, an ethylene-vinyl acetate film, an ethylene-propylene copolymer film, an ethylene-ethyl acrylate copolymer film, an ethylene-methyl acrylate copolymer film, or a polyimide film.
[0061] In addition, the coating method is not particularly limited as long as it can coat the polymer solid electrolyte solution on the substrate in the form of a film, and may be, for example, bar coating, roll coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating, or solution casting.
[0062] In the present invention, in the step (S3), the coating film can be frozen and thawed to form a crosslinked structure, i.e., in the freezing process, the bonds of (a), (b) and (c) are induced by the crosslinkable functional groups to form a crosslinked structure and an amorphous polymer chain.
[0063] In the freezing process, the polymer and water contained in the aqueous polymer solution containing the cross-linking functional group used to form the coating film may undergo phase separation. The phase separation may be induced due to the stronger hydrogen bonds between the water molecules than between the cross-linking functional group and the water molecules. The water molecules aggregated by the hydrogen bonds between the water molecules are present in an ice phase due to the freezing process. As a result, the number of cross-linking functional groups that form hydrogen bonds through interaction with the water molecules is significantly reduced.
[0064] That is, in the process of freezing the coating film, the polymer and water contained in the aqueous polymer solution must first undergo phase separation, and the phase separation can be induced by hydrogen bonds between water molecules.
[0065] Due to the phase separation, the inside of the coating film is divided into (i) a polymer-poor phase and (ii) a polymer-rich phase.
[0066] The (i) polymer-poor phase is a portion containing water molecules aggregated by hydrogen bonds between water molecules, and exists in an ice phase, which can also be called a free water state.
[0067] The (ii) polymer-rich phase is a portion containing a polymer that has been phase-separated from water. The phase-separated polymer is a polymer containing a cross-linking functional group that has been freed from interactions with water molecules, and after phase separation, it is in a free state, does not form crystals through regular folding, and exists in an amorphous state with relatively free behavior, which is called an amorphous polymer chain.
[0068] In addition, some of the cross-linkable functional groups contained in the phase-separated polymer form localized crystallites, which act as cross-linkable junction points to form a cross-linked structure including the bonds (a), (b), and (c).
[0069] In addition, in the thawing process after the freezing process, the ice contained in the (i) polymer poor phase melts and evaporates, thereby producing a polymer solid electrolyte with an increased free volume.
[0070] The freezing may be performed by appropriately selecting conditions that can freeze the coating film. For example, the freezing temperature may be -30°C to -10°C, and specifically, the freezing temperature may be -30°C or higher, -25°C or higher, or -23°C or higher, and may be -18°C or lower, -15°C or lower, or -10°C or lower. If the freezing temperature is lower than -30°C, cracks may occur in the coating film, and if it exceeds -10°C, phase separation between the polymer and water may not be sufficiently performed, making it difficult to form an amorphous polymer chain region. The freezing may be performed in consideration of a sufficient freezing time within a range of 20 hours to 30 hours.
[0071] The thawing may be performed under appropriately selected conditions that allow the frozen coating film to be thawed to an extent that it can be used as a polymer solid electrolyte. For example, the thawing temperature may be 15°C to 35°C, or may be room temperature (25°C). If the thawing temperature is less than 15°C, the efficiency of drying water after thawing (ice melting) may decrease, and if it exceeds 35°C, the coating film may shrink and wrinkle or warp may occur.
[0072] As described above, the freezing and thawing process induces the bonds of (a), (b) and (c) to form cross-linked structures and amorphous polymer chains.
[0073] Therefore, the degree of formation of the cross-linked structure can be adjusted by the number of times the freezing and thawing processes are performed. When the process of performing the freezing process and then the thawing process is defined as one cycle, the freezing and thawing process may be performed for one or more cycles, two or more cycles, three or more cycles, or five or more cycles. The upper limit of the cycle is not particularly limited, and may be 10 cycles or less, 13 cycles or less, or 15 cycles or less. As the number of cycles of the freezing and thawing process increases within the above range, the more cross-linked structures are formed, and thus the modulus and strength of the polymer solid electrolyte can be increased.
[0074] After the step (S3), the method may further include a step (S4) of supporting the polymer solid electrolyte in a liquid electrolyte and then drying the liquid electrolyte, the composition and content of which are as described above.
[0075] All solid state battery The present invention also relates to an all-solid-state battery including the polymer solid electrolyte, the all-solid-state battery including a negative electrode, a positive electrode, and a polymer solid electrolyte interposed between the negative electrode and the positive electrode, the solid electrolyte having the characteristics described above.
[0076] Specifically, the polymer solid electrolyte is suitable as an electrolyte for an all-solid-state battery because the crystallinity is reduced by forming physical cross-links through a freezing and thawing process, thereby improving ion conductivity.
[0077] In the present invention, the positive electrode included in the all-solid-state battery may include a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode current collector.
[0078] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.
[0079] The positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Li[Ni x Co y Mn z M v ]O2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In; 0.3≦x<1.0, 0≦y, z≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c(wherein, 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti; M' is at least one selected from the group consisting of Al, Mg, and B, and A is at least one selected from the group consisting of P, F, S, and N), or a compound substituted with one or more transition metals; 1+y Mn 2-y Lithium manganese oxides such as LiMnO4 (where y is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-y Ni-site type lithium nickel oxide represented by MyO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); chemical formula LiMn 2-y M y Examples of lithium manganese composite oxides include, but are not limited to, lithium manganese composite oxides represented by Li2Mn3MO8 (wherein M is Co, Ni, Fe, Cr, Zn, or Ta, and y is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.
[0080] The positive electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material may be 40 wt % or more or 50 wt % or more, and 70 wt % or less or 80 wt % or less. If the content of the positive electrode active material is less than 40 wt %, the connectivity between the wet positive electrode active material layer and the dry positive electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0081] The binder may further include, as a component that aids in binding the positive electrode active material to the conductive material and the like and in binding to the current collector, a rubber such as styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, The binder may include at least one selected from the group consisting of polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethylcellulose, hydroxypropylcellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylcellulose, cyanoethylsucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropene. Preferably, the binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.
[0082] The binder may be included in an amount of 1 wt% to 30 wt% based on the total weight of the positive electrode active material layer, and specifically, the binder content may be 1 wt% or more or 3 wt% or more, and 15 wt% or less or 30 wt% or less. If the binder content is less than 1 wt%, the adhesive strength between the positive electrode active material and the positive electrode current collector may decrease, and if it exceeds 30 wt%, the adhesive strength is improved, but the content of the positive electrode active material may decrease accordingly, and the battery capacity may decrease.
[0083] The conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery, does not induce chemical changes in the battery, and has excellent electrical conductivity. Typically, graphite or conductive carbon may be used. For example, graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, summer black, and other carbon blacks; carbon-based substances having a graphene or graphite crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives; may be used alone or in a mixture of two or more kinds, but are not necessarily limited to these.
[0084] The conductive material may be contained in an amount of 0.5 wt% to 30 wt% based on the total weight of the positive electrode active material layer. Specifically, the content of the conductive material may be 0.5 wt% or more or 1 wt% or more, and 20 wt% or less or 30 wt% or less. If the content of the conductive material is less than 0.5 wt%, the effect of improving electrical conductivity may be difficult to be expected, or the electrochemical properties of the battery may be deteriorated. If the content of the conductive material is more than 30 wt%, the amount of the positive electrode active material may be relatively small, and the capacity and energy density may be reduced. There is no particular limitation on the method of incorporating the conductive material into the positive electrode, and a conventional method known in the art, such as coating on the positive electrode active material, may be used.
[0085] The positive electrode current collector supports the positive electrode active material layer and transfers electrons between an external conductor and the positive electrode active material layer.
[0086] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the all-solid-state battery and has high electronic conductivity. For example, the positive electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.
[0087] The positive electrode current collector may have a fine uneven structure or a three-dimensional porous structure on the surface thereof in order to strengthen the bonding force with the positive electrode active material layer, and may have various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a nonwoven fabric, etc.
[0088] The positive electrode may be manufactured according to a conventional method, specifically, by mixing a positive electrode active material, a conductive material, and a binder in an organic solvent to prepare a composition for forming a positive electrode active material layer, applying the composition onto a positive electrode current collector, drying the composition, and optionally compressing the composition into a current collector to improve the electrode density. At this time, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, the binder, and the conductive material and that can be easily evaporated. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropyl alcohol, etc. may be used.
[0089] In the present invention, the negative electrode included in the all-solid-state battery may include a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.
[0090] The negative electrode active material is lithium (Li + The lithium-containing compound may include a material capable of reversible intercalation or deintercalation of lithium ions, a material capable of reversibly reacting with lithium ions to form a lithium-containing compound, lithium metal, or a lithium alloy.
[0091] The lithium ion (Li +The material capable of reversibly inserting or de-inserting lithium ions (Li) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium (Li) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0092] Preferably, the negative electrode active material is lithium metal, and more particularly, may be in the form of a lithium metal thin film or lithium metal powder.
[0093] The negative electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40 wt % or more or 50 wt % or more, and 70 wt % or less or 80 wt % or less. If the content of the negative electrode active material is less than 40 wt %, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0094] The binder is the same as that described above in the positive electrode active material layer.
[0095] The conductive material is the same as that described above in the positive electrode active material layer.
[0096] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and for example, the negative electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. Similarly to the positive electrode current collector, the negative electrode current collector may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., with fine irregularities formed on the surface.
[0097] The method for manufacturing the negative electrode is not particularly limited, and the negative electrode may be manufactured by forming a negative electrode active material layer on a negative electrode current collector using a layer or film forming method commonly used in the art. For example, methods such as compression bonding, coating, deposition, etc. may be used. In addition, the negative electrode of the present invention also includes a case where a thin metallic lithium film is formed on a metal plate by initial charging after assembling a battery without a thin lithium film on the negative electrode current collector.
[0098] The present invention also provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0099] In this case, specific examples of the device include, but are not limited to, power tools that are powered by a battery-type motor; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.
[0100] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical spirit of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.
[0101] In the following Examples and Comparative Examples, as shown in Table 1 below, polymer solid electrolytes were prepared depending on whether or not a crosslinkable functional group is included, the type of polymer containing a crosslinkable functional group, the molar ratio of the crosslinkable functional group to lithium ions, and whether or not a freeze / thaw process is applied.
[0102] [Table 1]
[0103] Example 1 PVA (Mw: 89,000 g / mol; degree of hydrolysis: >99%) was mixed with water to prepare a 10% PVA aqueous solution. LiTFSI was added to the PVA aqueous solution and stirred to prepare a solution containing PVA, a polymer having a cross-linking functional group, and LiTFSI, a lithium salt. At this time, the molar ratio ([Li] / [OH]) of the cross-linking functional group of the PVA, "OH", to the lithium salt, "Li", was set to 0.4.
[0104] The solution was applied to a substrate, SS foil, by bar coating to form a coating film, which was then frozen at -20°C for 24 hours and thawed at 25°C to prepare a polymer solid electrolyte.
[0105] Example 2 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that PVA having a weight average molecular weight (Mw) of 85,000 g / mol was used.
[0106] Example 3 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that PVA having a weight average molecular weight (Mw) of 100,000 g / mol was used.
[0107] Example 4 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [OH]) of the cross-linking functional group “OH” of the PVA to the “Li” of the lithium salt was 0.1.
[0108] Example 5 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [OH]) of “O” contained in the cross-linking functional group of PVA to “Li” of the lithium salt was 0.2.
[0109] Example 6 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [O]) of “O” contained in the cross-linking functional group of the PVA to “Li” contained in the lithium salt was 0.3.
[0110] Comparative Example 1 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that a solution containing PVA, a polymer having a cross-linkable functional group, and LiTFSI, a lithium salt, was applied onto a substrate, SS foil, and then dried at 80°C.
[0111] Comparative Example 2 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that PEO, a polymer having no cross-linking functional group, was used instead of PVA.
[0112] Comparative Example 3 A polymer solid electrolyte was prepared in the same manner as in Comparative Example 1, except that a solution containing PVA, a polymer having a cross-linkable functional group, and LiTFSI, a lithium salt, was applied onto a substrate, SS foil, and then dried at room temperature (25°C).
[0113] Comparative Example 4 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that a 35% aqueous solution of poly(acrylic acid, PAA) (Mw: 100,000 g / mol) was used instead of PVA.
[0114] Comparative Example 5 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that PVA having a weight average molecular weight (Mw) of 50,000 g / mol was used.
[0115] Comparative Example 6 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that PVA having a weight average molecular weight (Mw) of 146,000 g / mol was used.
[0116] Comparative Example 7 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [OH]) of “O” contained in the cross-linking functional group of PVA to “Li” of the lithium salt was 0.5.
[0117] Comparative Example 8 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [OH]) of “O” contained in the cross-linking functional group of PVA to “Li” of the lithium salt was set to 0.52.
[0118] Experimental Example 1 The ionic conductivity of the film-shaped polymer solid electrolyte prepared in the examples and comparative examples was measured using a 1.7671 cm 2The solid polymer electrolyte was punched out into a circle of the same size, and the punched solid polymer electrolyte was placed between two pieces of stainless steel (SS) to prepare a coin cell.
[0119] The resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25° C., an amplitude of 10 mV, and a scan range of 500 KHz to 20 MHz, and then the ionic conductivity of the polymer solid electrolyte was calculated using the following Equation 1.
[0120]
number
[0121] In the above formula 1, σ i is the ionic conductivity (S / cm) of the polymer solid electrolyte, R is the resistance (Ω) of the polymer solid electrolyte measured by the electrochemical impedance spectrometer, L is the thickness (μm) of the polymer solid electrolyte, and A is the area (cm 2 )
[0122] The ionic conductivity of the polymer solid electrolyte calculated using Equation 1, whether a freestanding film could be formed, and the results of observing the appearance of the polymer solid electrolyte are shown in Table 2. Here, whether the freestanding film could be formed (formed: ◯, not formed: ×) and the appearance of the polymer solid electrolyte were observed with the naked eye.
[0123] [Table 2A] [Table 2B]
[0124] As shown in Table 2, it was confirmed that a free-standing film-like polymer solid electrolyte can be produced by using PVA having an appropriate range of molecular weight and a molar ratio ([Li] / [OH]) of the cross-linkable functional group and the lithium contained in the lithium salt as the polymer containing the cross-linkable functional group and applying a freezing and thawing process (Examples 1, 2, 3, 5, and 6).
[0125] In Comparative Example 4, PAA was used as a polymer containing a cross-linkable functional group. After the formation of the coating film, the PAA froze during the freezing process and became liquid again during the thawing process, so that a free-standing film-like polymer solid electrolyte could not be produced.
[0126] In Comparative Example 5, the molecular weight of the PVA was low and the PVA was produced in a liquid state, and a free-standing film-like polymer solid electrolyte was not obtained.
[0127] In addition, in Comparative Example 6, the molecular weight of the PVA was high, and a solution for forming a coating film could not be obtained, so that the electrolyte production process could not be carried out.
[0128] In addition, in Example 4, a free-standing film-like polymer solid electrolyte was produced when observed with the naked eye, but the ion conductivity was significantly low and brittleness was also observed. This is because the molar ratio of the cross-linking functional group to lithium ([Li] / [OH]) was small, and although a cross-linked structure was formed, it was not sufficiently formed to be suitable for use in a polymer solid electrolyte.
[0129] In addition, in Comparative Example 7, the molar ratio of cross-linkable functional groups to lithium ([Li] / [OH]) was large, and a highly viscous gel was produced instead of a film. The gel had high ionic conductivity, but since it was in gel form rather than a film, it was confirmed that it was not suitable for use as a polymer solid electrolyte. A gel state refers to a solid state with such low mechanical strength that it cannot be peeled off from the substrate, or a highly viscous liquid state, making it difficult to use as a polymer solid electrolyte.
[0130] In addition, in Comparative Example 8, the molar ratio of cross-linkable functional groups to lithium ([Li] / [OH]) was larger than in Example 1, and a highly viscous gel was produced instead of a film. Although the gel had high ionic conductivity, it was confirmed that it was not suitable for use as a polymer solid electrolyte because it was in gel form rather than a film.
[0131] In Comparative Example 1, the electrolyte was prepared using a high-temperature drying process at 80° C., and a gel-like electrolyte with high viscosity was produced. A uniform coating film could not be formed on the substrate, and air bubbles, aggregation, and warping occurred during the formation of the coating film.
[0132] Comparative Example 2 was an electrolyte prepared using PEO that did not have cross-linking functional groups, and was in liquid form rather than in film form.
[0133] Comparative Example 3 is a polymer solid electrolyte prepared using a room temperature drying process. It was found that the polymer solid electrolyte had low mechanical strength and low ionic conductivity due to the absence of physical cross-links formed by the freezing and thawing processes.
[0134] FIG. 1 is a graph showing the tendency of the ionic conductivity of the electrolyte depending on the molar ratio ([Li] / [OH]) of the cross-linkable functional group to the lithium salt.
[0135] Referring to FIG. 1, the molar ratio of lithium to cross-linking functional groups ([Li] / [OH], n Li / n PVA It can be seen that the ionic conductivity of the polymer solid electrolyte increases as the value of ionic conductivity increases. Comparative Example 3 was prepared by a room temperature drying process, and it can be seen that the ionic conductivity was significantly low.
[0136] FIG. 2 is a photograph showing the electrolyte morphology depending on the molar ratio of cross-linking functional group to lithium ([Li] / [OH]).
[0137] Referring to FIG. 2, it can be seen that Example 4, in which the molar ratio of cross-linkable functional group to lithium ([Li] / [OH]) was 0.1, produced a brittle film, Comparative Example 7, in which the molar ratio was 0.5, produced a highly viscous gel, and Examples 1, 5, and 6, in which the molar ratio was between more than 0.1 and less than 0.5, produced film-shaped polymer solid electrolytes.
[0138] Example 7 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the freezing and thawing process was performed twice.
[0139] Example 8 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the freezing and thawing process was performed three times.
[0140] Example 9 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the freezing and thawing process was repeated five times.
[0141] Example 10 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the freezing and thawing process was repeated 10 times.
[0142] Comparative Example 9 PVA (Mw: 89,000 g / mol; degree of hydrolysis: >99%) was mixed with water to prepare a 10% PVA aqueous solution, which was then coated onto SS foil and dried at high temperature (90°C, 3 hours) to produce a PVA film.
[0143] Comparative Example 10 A PVA film was prepared in the same manner as in Comparative Example 9, except that boric acid was added as a crosslinking agent.
[0144] Experimental Example 2 An experiment was carried out to compare the presence or absence and the degree of formation of a cross-linked structure inside the polymer solid electrolyte.
[0145] Since the purpose of the present study was to compare only the presence or absence and the degree of formation of a cross-linked structure, the PVA film of Comparative Example 8, which did not contain a cross-linked structure, and the PVA film of Comparative Example 9, in which a chemical cross-linked structure was formed by a cross-linking agent, were used for comparison.
[0146] (1) Check the degree of swelling The test samples were immersed in water at room temperature (25°C) for 12 hours, and the degree of swelling of the samples was then confirmed and evaluated according to the following criteria.
[0147] <Criteria for determining swelling degree> ◎: Swelling of 80% or more of the total volume. ○: Swelling of 50% or more of the total volume. △: Swelling of 20% or more of the total volume. ×: Swelling of less than 10% of the total volume.
[0148] (2) Modulus The modulus was measured by a Universal testing machine (UTM).
[0149] [Table 3]
[0150] Referring to Table 3, Examples 1 and 7 to 10 are polymer solid electrolytes manufactured by a freezing and thawing process, and show modulus above a certain level, and as the number of cycles of the freezing and thawing process increases, the modulus also increases. In addition, as the number of cycles increases, the swelling degree also decreases. In general, the swelling degree and mechanical properties of a polymer are greatly affected by the degree of crosslinking. The formation of crosslinking points increases the internal resistance of the polymer chain, thereby inducing an increase in swelling resistance and mechanical strength. In particular, the formation of physical crosslinks based on the freezing-thawing process is affected by the number of repetitions of the freezing-thawing process. As the number of cycles increases, the modulus increases and the swelling degree decreases, and it can be seen that the crosslinked structure increases as the number of cycles increases. Although Example 1 shows that the swelling degree is 50% or more of the total volume, this is a result measured after 12 hours at room temperature, and is suitable as a property required for a polymer solid electrolyte for an all-solid-state battery.
[0151] It is seen that the PVA film of Comparative Example 9 was swollen to 80% or more of its total volume, which indicates that no cross-linked structure is present inside the polymer.
[0152] The PVA film of Comparative Example 10 had a chemical cross-linked structure formed by the addition of boric acid as a cross-linking agent, and it was found that the modulus was reduced compared to that of Comparative Example 9, in which no cross-linked structure was formed.
[0153] The PVA film of Comparative Example 10 had a reduced modulus compared to that of Comparative Example 9 due to the formation of a chemical cross-linked structure, reduced crystallinity, and increased polymer flexibility.
[0154] Meanwhile, Examples 1 and 7 to 10 correspond to hydrogel-like PVA films based on physical cross-linking formed using a freezing and thawing process, unlike the manufacturing methods of Comparative Examples 9 and 10. This shows a tendency that the modulus increases as the cross-linking increases. In Examples 1 and 7 to 10, the cross-linked structure increases as the number of freezing and thawing process cycles increases, and the modulus also increases. Through the freezing and thawing process, some of the cross-linking functional groups contained in the PVA form localized crystallites, and the localized crystallites act as cross-linkable junction points, increasing the modulus.
[0155] Although the present invention has been described above using limited examples and drawings, the present invention is not limited thereto, and it is obvious that various modifications and variations can be made by a person having ordinary knowledge in the technical field to which the present invention pertains within the technical spirit of the present invention and the equivalent scope of the claims described below.
Claims
1. A polymer solid electrolyte comprising a polymer having a cross-linking functional group, a lithium salt, and a solvent, The polymer solid electrolyte comprises an amorphous polymer chain having a cross-linked structure and the cross-linkable functional group, The cross-linked structure includes (a) a cross-link between the cross-linkable functional groups, (b) a cross-link between the cross-linkable functional groups and the solvent, and (c) a bond between the cross-linkable functional groups and a lithium salt.
2. the (a) cross-linking bond between the cross-linking functional groups comprises a hydrogen bond, (b) the cross-linking between the cross-linkable functional group and the solvent comprises a hydrogen bond; 2. The polymer solid electrolyte according to claim 1, wherein the bond between the cross-linkable functional group and the lithium salt (c) includes a bond based on Lewis acid-base interaction.
3. 2. The polymer solid electrolyte according to claim 1, wherein the cross-linkable functional group comprises at least one selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.
4. The polymers containing the crosslinkable functional groups include polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(ethylene oxide), poly(acrylamide), poly(acrylic acid) (PAA), starch-carboxymethyl cellulose, hyaluronic acid-methyl cellulose, and the like. The polymer solid electrolyte according to claim 1, which comprises at least one selected from the group consisting of N-isopropylacrylamide, N-isopropylacrylamide, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.
5. 2. The polymer solid electrolyte according to claim 1, wherein the weight average molecular weight (Mw) of the polymer containing the cross-linking functional group is 80,000 g / mol to 130,000 g / mol.
6. The polymers containing the crosslinkable functional groups include polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(ethylene oxide), poly(acrylamide), starch-carboxymethyl cellulose, hyaluronic acid-methyl cellulose, and the like. The polymer solid electrolyte according to claim 1, which comprises at least one selected from the group consisting of N-isopropylacrylamide, N-isopropylacrylamide, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.
7. The lithium salt is (CF 3 SO 2 ) 2 NLi (Lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), (FSO 2 ) 2 NLi (Lithium bis(fluorosulfonyl)imide, LiFSI), LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 C 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN, and LiC(CF 3 SO 2 ) 3 The polymer solid electrolyte according to claim 1, comprising one or more selected from the group consisting of:
8. 2. The polymer solid electrolyte according to claim 1, wherein the molar ratio ([Li] / [G]) of the cross-linking functional group ([G]) of the polymer to the lithium ([Li]) of the lithium salt is greater than 0.1 and less than 0.
5.
9. The polymer solid electrolyte according to claim 1 , wherein the solvent comprises water.
10. The polymer solid electrolyte according to claim 1 , wherein the polymer solid electrolyte is in the form of a freestanding film or a coating layer.
11. The ionic conductivity of the polymer solid electrolyte is 10 -4 2. The polymer solid electrolyte according to claim 1, which has a specific surface area of 1.5 S / cm or more.
12. The polymer solid electrolyte according to claim 1 , further comprising a liquid electrolyte.
13. (S1) adding a lithium salt to a polymer solution containing a cross-linkable functional group to form a polymer solid electrolyte forming solution; (S2) applying the polymer solid electrolyte forming solution onto a substrate to form a coating film; and (S3) a step of freezing and thawing the coating film.
14. The polymer solid electrolyte includes a cross-linked structure, the cross-linked structure includes (a) a cross-link between the cross-linkable functional groups, (b) a cross-link between the cross-linkable functional groups and a solvent, and (c) a bond between the cross-linkable functional groups and a lithium salt; the (a) cross-linking bond between the cross-linking functional groups comprises a hydrogen bond, (b) the cross-linking between the cross-linkable functional group and the solvent comprises a hydrogen bond; The method for producing a polymer solid electrolyte according to claim 13, wherein the (c) bond between the cross-linkable functional group and the lithium salt includes a bond due to Lewis acid-base interaction.
15. The method for producing a polymer solid electrolyte according to claim 13, wherein the freezing is carried out at −30° C. to −10° C.
16. The method for producing a polymer solid electrolyte according to any one of claims 13 to 15, wherein the thawing is carried out at 15°C to 35°C.
17. An all-solid-state battery comprising the polymer solid electrolyte according to any one of claims 1 to 12.
Citation Information
Patent Citations
Preparation method of high strength alkaline polymer electrolyte
CN110581315A
Gel electrolyte
JP1994150940A
Gel electrolyte
JP1994150941A
Polymer electrolytes and electrochemical devices comprising such polymer electrolytes
JP2008500693A
Single ion conductor cross-linked polymeric networks
US20030023001A1